Towards a Risk Management and Conservation Plan for the Djin Blocks at the World Heritage Site of Petra, Jordan: The Case of Djin Block No. 9. (3rd April 2015) - Haddad, Naif A.; Akasheh, Talal S.; Lerma, José L.; Khresat, Bilal R.
Abstract : Cultural heritage is subjected to many pressures and risks. Over the past few years, the use of digital technologies has significantly changed the approaches to cultural heritage documentation for the purpose of condition assessment and conservation. The integration of novel approaches and techniques has permitted a detailed examination and assessment of damage, deterioration due to weathering and erosion, and their mechanisms. This study seeks to contribute to the preservation and conservation of the significant heritage of the so-called Djin Blocks at the World Heritage Site of Petra in Jordan. While these three dimensional cuboid rock-cut monuments have been subject to extensive conservation studies, this is the first time they have been subjected to 3D recording and multispectral photography, with the aim of recording damage caused by the ravages of time. This study presents the results of the documentation of the case study Djin Block No. 9. A variety of systematic documentation techniques were used, including 3D recording with terrestrial laser scanning (TLS), close-range photogrammetry, multispectral imaging, and thermography records. In addition, pathological studies of the erosion from various causes and an analysis of the effect of weathering on Djin Block No. 9 are performed. Based on this data, the paper presents recommendations for developing risk management and conservation planning of Djin Block No. 9.